MANAGEMEN LABA AKRUAL DAN RIIL PADA PERUSAHAAN DELISTING DI EMPAT NEGARA ASEAN - , MAHARANI DHIAN KUSUMAWATI, SE., Indra Wijaya Kusuma, Prof. Dr., MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The purpose of this study was to obtain empirical evidence on earnings management actions undertaken by the delisted firms compared to listed firms and earnings management undertaken by the forced delisted firms compared to voluntary delisted firms. This study focused on delisted firms and using listed firms as the firms's control. This research was conducted in four ASEAN countries, namely Indonesia, Malaysia, Singapore, and Thailand. Thia study uses 71 delisted firms of 236 delisted firms in sample countries using purposive sampling method. This study used multiple linear regression to obtain the coefficients in the calculation of accruals earnings management and real earnings management in each country. To test the hypothesis of the study used independent sample t-test. Accrual earnings management was measured by discretionary accruals proxy using the modified Jones model introduced by Dechow et al. (1995). Real earnings management was measured by the proxy of real earnings management (REM), which is the sum of abnormal cash flow from operations, abnormal discretionary expenses, and abnormal production costs. Testing hypotheses using the pooled data and data of each country. The result show thatearnings management on delisted firms was not different with listed firms, so the first hypothesis was rejected. While testing the second hypothesis find that earnings management on forced delisted firms different from voluntary delisted firms, so the second hypothesis was supported. Accruals and real earnings management on voluntary delisted firms is higher than the forced delisted firms.